(untitled) (Jóvenes en la Ciencia, 2024)
Alternative therapies such as music therapy, yoga, etc., have been used to treat a variety of psychological problems, such as stress, anxiety and depression. Additionally, scientific research has increasingly supported the effectiveness of some alternative therapies in treating psychological problems. OBJECTIVE: To know the use and benefit of alternative therapies in the control of disorders such as anxiety, stress and depression in students. A questionnaire was applied whose sample was of convenience to the students of the Life Sciences Division. Among the ethical precautions, written informed consent was considered and the freedom of the interviewee to suspend the interview was emphasized. For the analysis of service use, therapies were grouped into two categories: self-care practices (home remedies, self-medication, physical activities, etc.) and alternative and/or complementary services (self-help groups, traditional Mexican medicine, spiritual counselors, etc. It was shown that, if they are usually used, some with more frequency and better results, among which the use of music therapy followed by meditation stands out, likewise by adopting a holistic approach, these therapies also seek to strengthen the comprehensive health of students, considering physical, emotional, mental and spiritual aspects. In conclusion, it was demonstrated that alternative therapies in students with psychological problems have proven to be an effective and beneficial tool to address the psychological needs of students.